The Effectiveness of Cognitive-Behavioral Training on Quality of Life and Anxiety Among Students of the Islamic Azad University, Shiraz Branch - Barati, Farima; Naseri, Ali (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to examine the effectiveness of cognitive-behavioral training on the quality of life and anxiety of university students.Methods and Materials: This quasi-experimental research employed a pretest-posttest design with a control group and a two-month follow-up. Through convenience sampling, 72 participants were selected and randomly assigned to two groups of 36 individuals. Both groups completed the Beck Anxiety Inventory and the World Health Organization Quality of Life Questionnaire (WHOQOL-BREF) at the pretest, posttest, and follow-up stages. The experimental group received cognitive-behavioral training over eight sessions. Finally, the data were analyzed using SPSS software, version 28.Findings: Findings from univariate and multivariate covariance analyses indicated that cognitive-behavioral training had a significant effect on both quality of life and anxiety at posttest and follow-up stages, with a significance level of (p < .05).Conclusion: Thus, it can be concluded that cognitive-behavioral training effectively improves the quality of life and reduces anxiety in university students.